SOCIO-ECONOMIC IMPLICATIONS OF MICRO CREDIT ON ECONOMIC DEVELOPMENT OF RURAL WOMEN IN NIGERIA - Dosunmu Akinola George; Ogunniyi Olayemi Jacob (European Scientific Journal, ESJ, 2015)
The study was undertaken to analyze the implications of micro credit experiences on rural women’s economic development. In general, rural development through women participation is the most important strategy designed to improve the social and economic life of the farming community in Nigeria, because their economic contribution is substantial (Izugbara, 2004). However, Parveen & Chaudhury (2009) argued that traditional labor division places on women, the primary responsibility of domestic chores as cooking, childcare, cleaning and fetching of water, amongst others. Invariably, women have limited access to markets, education; health care and economic services, which has led to a lower well-being of the family, which in-turn is believed to have retarded the developmental and traumatized the goals of the state. Put succinctly, micro credit is a system of small loans for incoming-generating activities, which enable poor communities to gain some economic stability (Chavan & Ramakumar, 2002). This paper seeks the historical relationship between micro credit programmes and economic hardship elimination of women, as it enhances their development in OtanAyegbaju, Boluwaduro local Government Area of Osun State. Ten in-depth interviews and 40 self-administered questionnaires were distributed to the participants of Better Life for Rural Women Programme in order to collect data. The paper argued that the context for understanding the position of micro credit based on the in-depth interviews support that the programmes should equally be extended to male folk. Recommendation and suggestions are given that if the micro credit programmes are strengthened it would involve male participation.